Youth Participatory Action Research as Culturally Sustaining Pedagogy. Issue 2 (3rd April 2018) - Walsh, Daniel
Abstract : In this article, I present the ways in which youth participatory action research (YPAR) provides opportunities for academically rigorous and culturally sustaining pedagogy for immigrant high school students learning English. In a course sponsored by the City University of New York's College Now program, I introduced students to the principles of critical ethnographic research and then guided them through the creation of a research proposal catalyzed by their own observations and questions of their immediate surroundings. A subset of this class of 15 was then mentored by me through the implementation of their research proposals, from question refinement to methods to data collection and analysis. Throughout the article, implications for teaching and learning for immigrant youth learning English are discussed.